STUDENTS' PERCEPTIONS ON READING COMPREHENSION DIFFICULTIES DURING THE TRANSITION TIME OF ONLINE-OFFLINE COURSES AT ENGLISH DEPARTMENT - Nurahmawati, Dwi Riski; Atmowardoyo, Haryanto; Samtidar, Samtidar (Universitas Negeri Makassar, 2023)
This research is a mixed research (Quantitative and Qualitative) that aims to determine students' perceptions of reading comprehension difficulties during the transition time of online-offline courses in the English department. The independent variable in this research is various kinds of reading comprehension difficulties, while the dependent variable is English language education students. The population in this research were all English language Education students at Universitas Negeri Makassar class of 2021, while the sample was 42 people from 7 classes, namely classes A, B, C, D, E, Pare-Pare, and Advanced Studies who filled out the questionnaire and 5 of them were interviewed. Research data was obtained by providing questionnaires and interviews. The questionnaire data was analyzed using SPSS 26 and the interview data was analyzed using data reduction, data display and conclusions. Based on the results of the questionnaire as quantitative analysis, data obtained from as much as 59.7% of the 100% sample of students experienced difficulties in reading comprehension class and based on the interview as qualitative data, it was stated that the entire sample of students experienced difficulties in reading comprehension class during the transition time of online-offline courses. Apart from that, there are 19 types of reading comprehension difficulties experienced by students and 3 types of reading comprehension difficulties that are most often experienced by students.